Creating a communication system from scratch: gesture beats vocalization hands down - Fay, Nicolas; Lister, Casey J.; Ellison, T. Mark; Goldin-Meadow, Susan (Frontiers in Psychology, 2014)
How does modality affect people’s ability to create a communication system from scratch? The present study experimentally tests this question by having pairs of participants communicate a range of pre-specified items (emotions, actions, objects) over a series of trials to a partner using either non-linguistic vocalization, gesture or a combination of the two. Gesture-alone outperformed vocalization-alone, both in terms of successful communication and in terms of the creation of an inventory of sign-meaning mappings shared within a dyad (i.e., sign alignment). Combining vocalization with gesture did not improve performance beyond gesture-alone. In fact, for action items, gesture-alone was a more successful means of communication than the combined modalities. When people do not share a system for communication they can quickly create one, and gesture is the best means of doing so.